The compact beam energy measurement method of the photocathode RF gun by the solenoid and beam shaping. - Bin Sun; Binkang Li; Xinjian Tan; Xiufeng Weng; Yu Wang; Faquan Wang; Jianxin Zhang; Hongqiao Yin; Xiaodong Zhang (PLoS ONE)
Beam energy, normalized emittance, and quantum efficiency are crucial parameters of the RF gun. In this study, we proposed a compact and low-cost method to measure the beam energy at the exit of the 120 MeV electron linac's RF gun. We utilized a solenoid magnetic field to rotate an elliptical beam and measured the rotation angle of the beam to calculate the energy. To generate an elliptical electron beam, we inserted a slit device after the laser beam shaping aperture (BSA) to produce a long strip of driving laser beam for the RF gun photocathode. During the measurement process, we employed the Maximally Stable Extremal Regions (MSER) detection algorithm to measure the beam spot angle, improving the accuracy and stability of the angle measurement. This method does not require any changes to the accelerator lattice, nor does it require additional space. It only requires inserting a slit device to measure the beam's energy. Our results indicated that the energy at the exit of the RF gun was 4-5 MeV, consistent with simulation calculations using ASTRA.